2019
DOI: 10.1186/s13031-019-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Violent conflict and breastfeeding: the case of Iraq

Abstract: BackgroundThis study explores the relationship between armed conflict and breastfeeding practices of Iraqi mothers. To date, the relationship between violent conflict and breastfeeding is surprisingly understudied. Especially in the Middle East, which is conflict-prone and has a young population, research on war and household behavior is critical for promoting recovery and sustainable development.MethodsThis study employs a unique pairing of the Iraq Body Count Database and the 2006 and 2011 Multiple Indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…9 In another study conducted in Iraq, it was reported that conflict intensity was negatively associated with breastfeeding incidence. 10 The breastfeeding behaviors of migrant mothers were found to be different from those of the host community mothers. The findings of this study also supported that the breastfeeding behaviors of mothers who migrated due to war were not at the desired level.…”
Section: Discussionmentioning
confidence: 98%
“…9 In another study conducted in Iraq, it was reported that conflict intensity was negatively associated with breastfeeding incidence. 10 The breastfeeding behaviors of migrant mothers were found to be different from those of the host community mothers. The findings of this study also supported that the breastfeeding behaviors of mothers who migrated due to war were not at the desired level.…”
Section: Discussionmentioning
confidence: 98%
“…Breast feeding declined significantly in regions with high levels of conflict-related violence relative to areas which were considered the ‘safest areas’ in Iraq. 29 A mother residing in dangerous areas of Iraq was 17.4% more likely to stop breast feeding compared with mothers living in the safe areas. 29 In Bosnia-Herzegovina, illness of mother/baby disrupted breast feeding and a few mothers made a personal decision not to breast feed.…”
Section: Resultsmentioning
confidence: 97%
“… 29 A mother residing in dangerous areas of Iraq was 17.4% more likely to stop breast feeding compared with mothers living in the safe areas. 29 In Bosnia-Herzegovina, illness of mother/baby disrupted breast feeding and a few mothers made a personal decision not to breast feed. 35 Other reasons that negatively affected breast feeding practices in conflict affected areas were unavailability of trained healthcare professionals, and disruption in knowledge created by violent conflict.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations